Anchoring Resilience in Faith: A Phenomenological Study of Muslim Smart ABA Therapists in Autism Care: Study on Muslim Therapists - Indrawati, Erdina; Arneliza, Arneliza; Zeb Khattak , Alam; Teguh Yunanto, Kuncono (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstrak: While resilience in Autism Spectrum Disorder (ASD) research is predominantly parent-centric, the emotional labor and professional longevity of therapists remain critically under-studied. This phenomenological study explores the resilience mechanisms of Muslim Smart Applied Behavior Analysis (ABA) therapists operating within a majority-Muslim cultural context. Through in-depth thematic analysis, we identify a dynamic resilience ecosystem anchored by five interconnected pillars: religiosity, patience (sabr), positive work affect, professionalism, and clinical success. Our primary discovery reveals that religiosity functions as a metacognitive framework that reinterprets clinical challenges as spiritual opportunities, thereby buffering against compassion fatigue and sustaining professional rigor. By integrating cultural and religious dimensions into the resilience discourse, this study challenges Western-centric, secular models of clinical endurance. These findings provide a strategic foundation for developing culturally-responsive supervision and training programs that leverage spiritual meaning-making to enhance therapist retention and well-being  Keywords: Autism Spectrum Disorder, muslim therapists, resilience; Smart ABA, religiosity